Impact of COVID-19 on deaths from respiratory diseases: Panel data evidence from Chile - Barría Sandoval, Claudia.; Ferreira, Guillermo; Méndez, Angie; Toffoletto, María Cecilia (Taylor and Francis Ltd., 2022)
The COVID-19 pandemic has relegated pathologies that were previously common- place to a secondary context. Therefore, it is necessary to study the evolution of these diseases in the presence or absence of COVID-19.
Keywords: Respiratory diseases; Panel data regression analysis panel data regression analysis; SARS-CoV-2